Analysis of Crimes of Violence against Children in Gorontalo Province - Hadju, Moh. Tri Mulya; Makkulawuzar, Kindom; Rusmulyadi, Rusmulyadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Currently, many criminal acts are often committed, such as violence. Violence is an arbitrary act committed by someone with the aim of causing physical or psychological harm. Parents have an important role to protect and protect, but instead acts of violence against children are carried out by those closest to them, such as parents. Child Victims of violence who are part of a society whose development is immature both physically and psychologically require special assistance in handling it. This study aims to determine the emergence of factors that cause victims of physical violence against children in the Gorontalo region to reduce the number of victims of acts of violence against children. Which examines the existence of violence perpetrated against children. Data collection was done by interview technique. So a way is needed so that acts of violence against children are not continuously carried out and strict action must be given by the government to the perpetrators who commit violence. So it is deemed necessary to emphasize the regulations that have been implemented in the government, especially Law Number 23 of 2002 concerning child protection